Digital Shopping Rush: A Scoping Review of Flash Sale and Free Shipping as Drivers of Impulse Buying in E-Commerce - Anggita Putri Indadari; Ardy Firmansyah; Prasetyo Wimar (Eastasouth Institute, 2026)
This article aims to analyze and map previous studies that examine the influence of flash sale and free shipping promotion strategies on impulse buying behavior within e-commerce platforms in Indonesia. This study uses a scoping review approach by analyzing 12 empirical studies published between 2020 and 2025. The results of the analysis show that most studies have found an important role of flash sales in encouraging impulse purchases because they create a sense of urgency and scarcity. Meanwhile, the free shipping strategy has also been shown to trigger impulse purchases because it reduces barriers in the form of additional costs, although the impact varies according to the context and in combination with other promotional strategies. This article provides a theoretical contribution by offering a comprehensive literature mapping of the relationship between flash sales, free shipping, and impulse buying behavior, so that it can be a foundation for the development of conceptual models as well as research directions in the field of digital consumer behavior and e-commerce marketing strategies.